Development of a rapid LFA test based on direct RT-LAMP for diagnosis of SARS-CoV-2 - Negar Sadeghi; Neda Shirazi; Moein Dehbashi; Bahareh Maleki; William C. Cho; Zohreh Hojati (Practical Laboratory Medicine)
Introduction: In response to the rapid spread of the SARS-CoV-2 virus, we developed a rapid molecular approach to diagnose COVID-19 without the need for RNA extraction. Methods: The study utilized two molecular methods, RT-qPCR and colorimetric RT-LAMP, to diagnose the RdRp and ORF8 genes, respectively, in oro-nasopharyngeal swabs. Due to the high sequence diversity of ORF8 in SARS-CoV and SARS-CoV-2, it has been identified as a suitable target for virus detection. The RT-LAMP method was also carried out directly on heat-treated swab samples. The strip tests were made using gold nanoparticles and combined with the RT-LAMP for further analysis. Results: The results showed that the isothermal amplification method had a sensitivity of 95 % (95 % C.I.: 86.08 %–98.96 %) and a specificity of 75 % (95 % C.I.: 19.41 %–99.37 %). The RT-LAMP-LFA method was able to distinguish positive and negative samples with 100 % sensitivity (95 % C.I.: 91.96–100) and 77.27 % specificity (95 % C.I.: 54.63–92.18). This method only required heating swab samples for 10 min at 65 °C before the RT-LAMP reaction. Conclusion: By utilizing the RT-LAMP in combination with the LFA, it is possible to diagnose SARS-CoV-2 rapidly without the need for RNA extraction. The entire process from sample collection to test interpretation takes only 75–90 min, and the results can be interpreted by untrained individuals with the naked eye. By employing the ORF8 gene as a diagnostic target and eliminating the need for RNA extraction, the direct RT-LAMP-LFA method achieves a significant breakthrough that was not previously reported.